2014
DOI: 10.1016/j.mspro.2014.07.126
|View full text |Cite
|
Sign up to set email alerts
|

Friction Stir Welding of Metal Matrix Composite Using Coated Tool

Abstract: Friction stir welding (FSW) is a solid state joining technique that has expanded rapidly since its development and has found applications in a wide variety of industries. In the present investigation work, friction stir weldabilty of 5% SiC particulate aluminum matrix cast composite using TiAlN coated tool and effect of process parameters such as tool rotation speed, traverse speed, and axial force on ultimate tensile strength were investigated. The result showed that there was no noticeable tool wear, only al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…One type of graph shows highest value of hardness in the stirred zone and its goes on decreasing along TMAZ and HAZ, and shows minimum value in the base material region as shown in Fig. 5 [24,26,27,31,[33][34][35]. Refinement of grain caused by dynamic recrystallization and proper distribution of particles due to the severe stirring action of FSW tool, results in higher hardness at the stirred zone.…”
Section: Micro Hardness Of Jointsmentioning
confidence: 96%
See 1 more Smart Citation
“…One type of graph shows highest value of hardness in the stirred zone and its goes on decreasing along TMAZ and HAZ, and shows minimum value in the base material region as shown in Fig. 5 [24,26,27,31,[33][34][35]. Refinement of grain caused by dynamic recrystallization and proper distribution of particles due to the severe stirring action of FSW tool, results in higher hardness at the stirred zone.…”
Section: Micro Hardness Of Jointsmentioning
confidence: 96%
“…Fine equi axed grains are observed in stirred zone which is smaller than the base material grain size, indicates nucleation of new grains in this zone [32]. Wang et al [33] observed high energy point on the broken surface of reinforced material (Sic) is the area of the nucleation and growth of the grains.…”
Section: Microstructure Of Fsw Zonementioning
confidence: 98%
“…It is a metal joining technique named friction stir welding developed to weld aluminum, magnesium and other lightweight materials [4]. Friction stir welding ability of 5% SiC particulate aluminum matrix cast composite…”
Section: Figure 1: Schematic Representation Of the Fsw Process [2]mentioning
confidence: 99%
“…Devanatha et al obtained enhanced life of steel tools used for FSW processes of welding metal matrix composite materials using the anti-wear TiAlN coating [28].…”
Section: Introductionmentioning
confidence: 99%